Case Study of Old Steel Riveted Railway Truss Bridge: From Material Characterization to Structural Analysis - Ambroziak, Andrzej; Malinowski, Maciej (The Baltic journal of road and bridge engineering, 2023)
The structural analysis of an old steel riveted railway truss bridge located over the Maruska River on the Działdowo – Olsztyn, Poland railway line is performed in this paper to check its behaviour under today’s railway loads. The mechanical properties of construction steel extracted from the old steel bridge are investigated by tensile tests, impact tests through the Charpy pendulum impact V-notch, and an optical emission spectrometer. Structural analysis exhibits that the steel bridge requires proper structural bridge improvements to meet today’s load requirements in terms of bearing capacity and serviceability state. The paper begins with a wide survey of literature carried out on the investigation of steel riveted railway bridge subject matter. This paper can provide scientists, engineers, and designers with an experimental and structural basis in the field of old steel riveted railway truss bridge construction.